이중 킬 요트의 저항 특성에 관한 연구 - 이유신(You-Shin Lee); 정우철(Uh-Cheul Jeong); 김규선(Kyu-Sun Kim); 박제웅(Je-Woong Park); 김도정(Do-Jung Kim); 박경훈(Kyung-Hun Park) (Han-guk haeyang gonghak hoeji (Online), 2011)
The resistance performances of a small leisure yacht with two different keels, center and double, respectively, are investigated using a model test at circulating water channel and CFD analysis. Flow patterns around the keels are observed using a tuft test to make clear the relation between the resistance performance and the flow characteristics around the keels. The results show that the keel does not affect free surface flows and that the double keel yacht has better performance compared to a single keel yacht in oblique condition from the resistance point of view.